2017
DOI: 10.1002/cam4.1175
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel prognostic invasive lesion index in ductal carcinoma in situ with minimal invasion of the breast

Abstract: Multiple invasive foci has been shown to increase the risk of lymph node metastasis (LNM) in early breast cancer, but its prognostic implication remains unknown. We aimed to identify the prognostic value of the number of invasive foci in ductal carcinoma in situ with minimal invasion of the breast (DCIS‐MI), and further establish a prognostic invasive lesion index (ILI). A total of 193 patients with DCIS‐MI (the invasive component was up to 10 mm in diameter) were included. Univariate and multivariate analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…There was no difference in regional recurrence rates after 10 years between the DCIS-MI group and the DCIS group (8.3% vs. 6.8%) 18 . DCIS-MI often has multiple minimally invasive foci, associated with a higher risk of ipsilateral recurrence 27 , 28 . The study by Si et al showed that 35.1% of DCIS-MI Patients have multiple foci, which had a worse disease-free survival rate compared with one-focus patients (98.29 vs. 93.01%, P = 0.032) 24 .…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in regional recurrence rates after 10 years between the DCIS-MI group and the DCIS group (8.3% vs. 6.8%) 18 . DCIS-MI often has multiple minimally invasive foci, associated with a higher risk of ipsilateral recurrence 27 , 28 . The study by Si et al showed that 35.1% of DCIS-MI Patients have multiple foci, which had a worse disease-free survival rate compared with one-focus patients (98.29 vs. 93.01%, P = 0.032) 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Even in the age group with the highest recurrence rate, 10-year locoregional recurrence remains low at 4.2% [25]. DCIS-MI often has multiple minimally invasive foci, associated with a higher risk of ipsilateral recurrence [26,27]. showed that the BCS + RT group showed signi cantly higher OS and BCSS than patients in the mastectomy group.…”
Section: Discussionmentioning
confidence: 99%